2004
DOI: 10.1111/j.0141-9854.2003.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening for sickle cell disease in Brazil: the Campinas experience

Abstract: Newborn screening for sickle cell disease commenced in 1992 in Sao Paulo State and by the end of 2000, the programme covered 78 institutions in 36 municipalities with the screening of 281,884 babies. Initially based on liquid cord blood samples, these are being replaced by dried filter paper capillary samples to ease handling and avoid diagnostic confusion from maternal contamination. The prevalence of sickle cell trait (2.0%) and HbC trait (0.6%) increased significantly between 1996 and 2000, apparently becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1
7

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 5 publications
0
24
1
7
Order By: Relevance
“…The estimated incidence for sickle-cell disorders is 1:2043 (1:1196-1:39 107) over a total population of 5 136 877 newborns screened (Brandelise et al 2004;Januario 2003;Lobo et al 2003;Sommer et al 2006), it being likely that the lowest incidences correspond to states located in the south of the country, which correlates with the characteristics of the ethnics groups inhabiting the region (see Electronic Supplementary Material available on-line).…”
Section: Comparative Analysis Of Features Of Newborn Screening Activimentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated incidence for sickle-cell disorders is 1:2043 (1:1196-1:39 107) over a total population of 5 136 877 newborns screened (Brandelise et al 2004;Januario 2003;Lobo et al 2003;Sommer et al 2006), it being likely that the lowest incidences correspond to states located in the south of the country, which correlates with the characteristics of the ethnics groups inhabiting the region (see Electronic Supplementary Material available on-line).…”
Section: Comparative Analysis Of Features Of Newborn Screening Activimentioning
confidence: 99%
“…Particularly in terms of the screened diseases, in those countries that have had national programmes (Botler et al 2003;Pinto et al 2005), Chile (Cornejo and Raimann 2004;Cornejo et al 1995Cornejo et al , 2003b, Costa Rica, Cuba, Guatemala, Paraguay and Venezuela have implemented such screening in a systematic way. Other diseases such as cystic fibrosis (CF) (Borrajo 2003;Domingos et al 2003), galactosaemia, congenital adrenal hyperplasia (CAH), biotinidase deficiency (Neto et al 2004), maple syrup urine disease (MSUD), haemoglobinopathies (Brandelise et al 2004;Lobo et al 2003;Sommer et al 2006) and glucose-6-phosphate dehydrogenase deficiency (G6PDD) are also screened in some countries. Aminoacidopathies, organic acidurias (OA) and fatty acid oxidation (FAO) deficiencies detected by MS/MS are screened in a massive way only in Costa Rica, and at a much lower rate in other countries in the private sector and on request (Schenone 2005) (Table 4).…”
Section: Comparative Analysis Of Features Of Newborn Screening Activimentioning
confidence: 99%
“…The study reported the prevalence of Hb AS in 1.98% of newborns and Hb SS in 0.01%. (12) The study of Ribeirão Preto reported Hb AS in 2.6% and Hb SS in 0.015% with high relevance, because the coverage was on average 94.5% of live births (figure indicated in the study). (9) In the west of São Paulo State there was a prevalence of 2.35% of Hb AS and 0.004% of Hb SS with medium relevance because the study was conducted in 168 cities of the state of São Paulo, the equivalent of 35% of all cities, with the sample size between 10,000 and 100,000.…”
Section: Discussionmentioning
confidence: 85%
“…(2) In 2001, the Ministry of Health established the National Program for Neonatal Screening (NPNS) within the Brazilian National Health System (SUS). This program is implemented in three phases and aims to nationally screen for four diseases; each state is classified based on its coverage and infrastructure: Phase I - congenital hypothyroidism and phenylketonuria, phase II - congenital hypothyroidism, phenylketonuria and hemoglobinopathies; Phase III - congenital hypothyroidism, phenylketonuria, hemoglobinopathies and cystic fibrosis.…”
mentioning
confidence: 99%